SYSTEMATIC REVIEW WITH META-ANALYSIS OF OBESITY AS RISK FACTOR OF COVID-19 RELATED MORTALITY - Rizwani, Achmad Ilham; Ahyandi, Syarif Syamsi; Naimatuningsih, Nanning; Ridwan, Endy Novryan; Nurvita, Rani; Nujum, Nurun; Mahrus, Muhammad Hammam; Djuari, Lilik (Universitas Airlangga, 2021)
A person with obesity has a high risk of getting a severe complication of COVID-19. This is related to the increasing of chronic illness cases caused by obesity. Obesity itself has been known to take part in the disruption of the human immune system. A person with obesity will be more susceptible to the infection and is suspected to be one of the risk factors that cause death in COVID-19. This study used observational analysis with a systematic review method and continued with Meta-Analysis. This study has been held at the Public Health Department of Faculty of Medicine, Universitas Airlangga, Surabaya, in July 2020. The data sources of this study come from online literature, such as published journals that match our inclusion criteria. The inclusion criteria for this study were journals that study the relation of obesity and mortality in COVID-19 cases, journals with a cross-sectional design, journals that used samples age >18 y.o., and journals that used BMI as the obesity classification. Five journals matched our criteria and were analyzed in this study. Four of 5 journals show that there is a relationship between obesity and mortality of COVID-19. There are 2133 subjects with COVID-19, and 361 of them have obesity. There are 1861 subjects with COVID-19 who are not dead; 1567 of them don't have obesity. An analytic study with a random effect model shows that obesity is the risk factor of mortality in COVID-19 cases (OR = 2.041; 95% CI 1.027-4.058). It also shows that there is a significant relationship between obesity and mortality in COVID-19 cases (p=0.042). Most journals analyzed with a systematic review and meta-analysis in this study show that obesity is the risk factor of mortality in COVID-19 cases.